Trees of the Central Valley of Costa Rica: reproduction guaba (Inga marginata Willd.) - Rojas-Rodríguez, Freddy (2018)
The following issue presents a brief description about the “guaba” tree (Inga marginata Willd.), including information about its phenology which directly relates to fruit recollection, seed treatment, nursery, and germination processes.